The Ethanol Extract of Polyscias scutellaria (EEPS) Shows Anti-Inflammatory Signaling Pathway Against LPS-Induced Inflammation in RAW 264.7 Macrophages - Nguyen, Nguyet Thi Anh; Selvaraj, Baskar; Vu, Huong Thuy; Nguyen, Qui Ngoc Sang; Oanh, Le Hong; Lee, Heesu; Tran, Quang Luc; Oanh, Vu Thi; Jung, Sang Hoon; Thuong, Phuong Thien; Lee, Jae Wook (SAGE Publications, 2025)
Aim of the Study This study investigates the anti-inflammatory effects of Polyscias scutellaria root ethanol extract (EEPS). The anti-inflammatory effects of the root samples, along with the molecular mechanisms behind these effects, are explored, including the involvement of the MAPK and NF-kappa B pathways and the release of pro-inflammatory cytokines. Furthermore, this study explores the isolation and identification of the active compounds present in the EEPS extract.Methods The anti-inflammatory effect was studied using LPS-induced inflammation in RAW 264.7 macrophages. EEPS extract was prepared using 70% ethanol, and LPS-induced pro-inflammatory factors such as nitric oxide (NO), iNOS, and COX-2 were analyzed using the Griess reagent and immunoblotting. The pro-inflammatory cytokines expressions IL-1 beta, IL-6, and TNF-alpha were studied by qPCR. Intracellular ROS and Ca2+ accumulation induced by LPS were assessed using DCF-DA and Fluo-3 AM fluorescent dyes. The LPS-induced NF-kappa B and MAPK pathways were also studied by immunoblotting. The active compounds present in this EEPS were isolated, and their structures were identified using NMR techniques.Results EEPS significantly inhibited these effects. EEPS also reduced LPS-induced expression of pro-inflammatory cytokines IL-1 beta, IL-6, and TNF-alpha. Immunoblot data revealed that EEPS suppressed NF-kappa B activation by preventing the phosphorylation of p65 and I kappa B-alpha as well as inhibited the phosphorylation of MAPK proteins ERK, p38, and JNK. Furthermore, EEPS reduced LPS-induced intracellular accumulation of ROS and Ca2+ in RAW 264.7 macrophages. From EEPS, we isolated 7 compounds. Among these, the saponin derivatives exhibited significant anti-inflammatory activity, reducing NO production by 60%similar to 70% in RAW 264.7 cells compared to LPS-treated cells.Conclusion EEPS exhibits strong anti-inflammatory effects in LPS-induced inflammation in RAW 264.7 cells by inhibiting the release of NO, iNOS, and COX-2 and preventing the activation of the NF-kappa B and MAPK pathways. This study is the first to highlight the anti-inflammatory potential of P. scutellaria root extract.